Corporate layoffs during the COVID-19 pandemic: the moderating role of social responsibility and governance - Fatmy, Veda (Springer Science+Business Media, 2026)
In this paper, I examine the effects of a firm’s past corporate social responsibility (CSR) on the involuntary turnover of its employees during the first year of the COVID-19 pandemic. Specifically, for 3,011 publicly traded US firms over the period 2013–2020, I determine differences in announced layoffs across firms with a history of above and below par social performance. CSR comprises several metrics of employee treatment and well-being, which bespeaks a corporate culture that attracts talented workers, and improves productivity for labor and recruitment costs. This would suggest that employees in socially responsible companies are less likely to be considered replaceable. On the other hand, downsizing may be more accessible to high-CSR firms because they have superior managerial agility and organizational capabilities. Consistent with the latter theory, the findings of this paper suggest that past corporate social performance is significantly and positively related to layoffs during the COVID-19 pandemic, which adds important evidence to the contextualization of CSR’s strategic capabilities for recruitment and management.
Keywords: Economic crisis; Layoffs; Employee turnover; Corporate social responsibility; Corporate governance; fi=Rahoitus|en=Finance|